Speeches. - Hockey, Joe; Turnbull, Malcolm, 1954-; Centre for Independent Studies (Australia) (St Leonards, NSW. : Centre for Independent Studies, 2011)
Speeches addressed to the Centre for Independent Studies.
Title from title screen (viewed on 1 August 2013)
Mode of access: Available online. Address as at 29/11/13
Selected for archiving
Keywords: Global Financial Crisis, 2008-2009.; Political planning -- Australia; Australia -- Politics and government; Australian